Pembaharuan dan Perubahan Nilai-Nilai Pancasila dalam Kehidupan Berbangsa dan Bernegara - . Sulistyanto (JURNAL CITRA WIDYA EDUKASI, 2019)
This paper tries to give a philosophical answer towards problem of dynamics in Pancasila. It is expected able to give justification for Pancasila; so that it will enrich teoritical sides and develop Pancasila praxis as natonal foundation and ideology of Indonesian people. It is hoped that this paper will give a contribution for keeping consistency, relevance, and contextualization of Pancasila is always needed by Indonesian people who are continuously developing according to world development. The realization of the expectation will make Pancasila able to play a role: internally, it functions as a glue of unity and union of Indonesian people and directs nation struggle towards its ideals. Externally, it functions as a nation identity so that Indonesian people are different from other people.